Sociodemographic characteristics as suicide risk factors in Belgrade, the capital of Serbia - Nikolić-Balkoski Gordana; Leposavić Ljubica (Vojnosanitetski Pregled)
Background/Aim. Suicide and self-inflicted injuries are one of the leading causes of injury-related deaths worldwide. The aim of this work was to investigate sociodemographic characteristics as a risk factor for suicide. The investigation covered the period from 1997 to 2011 on the territory of the capital of Serbia, the city of Belgrade. Methods. The data was taken from the index books of suicides committed in the city of Belgrade, held at the Institute of Informatics and Statistics. Statistical analysis was done by using the crude specific rate. The variability of the rate was estimated by computing a confidence interval. Results. The average suicide rate in the observed period was 9.88. The suicide rate has shown a regular decline until 2005, and since then, a mild growth was observed (the highest in 2000, the lowest in 2004). The results of our study pointed out the following sociodemographic profile as a risk factor for suicide: male with uncompleted elementary school who lives in a suburban community, aged 66 and over. Suicides were usually realized in the area of residence during the day, in late spring, and hanging was the most frequent method of suicide. Conclusion. Preventive public health measures should be implemented focusing on typical socio-demographic profile. Prospective studies should include more variables in order to identify more risk factors for suicide and suicidal behavior. To achieve this goal, a serious national strategy for recording suicide and suicide prevention would have to be developed.